FOR A SOCIOLOGY OF THE MEDITERRANEAN - Francesco Vespasiano (Economy and Sociology)
The great metamorphosis of the main sociological factors challenges us to abandon the presumption of colonization and the paradigm of the clash of civilizations and invites us to become aware of the changing demographic, political, economic, and cultural reality, and commits us to adopt a new analytical paradigm to understand and manage the transformation. The article proposes a synthetic analysis of this change, starting with statistical data on the migration of populations from the poorest countries on Earth to the richest ones. The analysis focuses on what is happening in the vast area of the Mediterranean. The history of the Mediterranean, this is the hypothesis put forward in the article, could help us to reflect innovatively on the demographic and cultural dynamics that are taking place in a particularly significant way. The reason for which it is hypothesized that the Mediterranean could be the privileged social place where we can reflect on the metamorphosis we are experiencing lies in the long tradition of welcoming diversity and in the capacity for the coexistence of religions, cultures, and civilizations that, over the centuries, have been the force thanks to which the whole world has been dominated, despite the clashes that historiography has unquestionably shown us. The article shows the important commitment of the leaders of the different world religions in generating spaces for encounters and dialogue between cultural diversities that cannot be analyzed within the paradigm of confrontation but require to be understood within the paradigm of confrontation and responsible coexistence. The work done so far clearly shows the possibility of dialogue between diversities, as well as pointing the way forward to socialize all different cultures to be together, without clashing for dominance; in this task, the reflections of Pope Francis and Edgar Morin on the concepts of brotherhood and fraternity appear particularly useful.